Prevalence of echinococcus granulosus as factor of risk of hydatidosis in sheep in the district of Ninacaca-Cerro de Pasco 2012 - Escobedo Bailón, Christian (2017)
The present study takes for objetive determine the prevalence of Echinococcus granulosus as a risk factor for the presentation of hydatidosis in sheep in the District of Ninacaca-Cerro de Pasco, during the period 2012. Design an epidemiological study of prevalence; descriptive observation of cross section where related prevalence of taenia Echinococcus granulosus having as definitive host the dog as a risk factor for the presence of hidatidicos cysts in sheep in the District of Ninacaca-Cerro de Pasco. 104 Shepherd dogs stool samples were taken for that reason. The data were obtained through surveys applied to cattle producers in the district, also was used an observation guide in order to register the results of the stool test of each unit of analysis. Tables of frequencies and the Chi square test were used to correlate these variables. It was noted that the prevalence of the Echinococcus granulosus was 45.2 % which corresponded to 47 dogs and the prevalence in the presentation of hydatid cysts was 30.8 % of a total of slaughtered sheep 104; Similarly it was observed that slaughtered sheep 24 representing 23.1% had these cysts to liver level, while slaughtered ovine 13 which represents 12.5% had level lung cysts. Significant differences were also found between the presence of the Echinococcus granulosus with the presentation of hydatid cysts in sheep slaughtered reasons for the study. (P≤0, 000).